Development characteristics of the box‐tree moth Cydalima perspectalis and its potential distribution in Europe. (8th October 2013) - Nacambo, S.; Leuthardt, F. L. G.; Wan, H.; Li, H.; Haye, T.; Baur, B.; Weiss, R. M.; Kenis, M.
Abstract The box‐tree moth Cydalima perspectalis (Walker) is an invasive pest causing severe damage to box trees (Buxus spp.). It is native to Japan, Korea and China, but established populations have been recorded in a number of locations across Europe since 2007 and the spread of the insect continues. The developmental investigations suggest that larvae overwinter mainly in their 3rd instar in Europe and that diapause is induced by a day length of about 13.5 h. One and a half to 2 months in the cold are necessary to terminate diapause. Threshold temperatures for development and number of degree‐days to complete a generation are slightly different from those calculated in previous studies in Japan. A bioclimatic (CLIMEX®) model for C. perspectalis in Europe was developed, based on climate, ecological and developmental parameters from the literature and new field and laboratory studies on diapause termination, thermal requirements and phenology. The model was then validated with actual distribution records and phenology data. The current distribution and life history of C. perspectalis in Europe were consistent with the predicted distribution. The climate model suggests that C. perspectalis is likely to continue its spread across Europe, except for Northern Fenno‐Scandinavia, Northern Scotland and high mountain regions. The northern distribution of C. perspectalis is expected to be limited by a number of degree‐days above the temperature threshold insufficient to complete a generation, whereas its southern range is limited by the absence of a cold period necessary to resume diapause. The model predicts relatively high Ecoclimatic Indices throughout most of Europe, suggesting that the insect has the potential of becoming a pest in most of its predicted range. However, damage is likely to be higher in Southern and Central Europe where the moth is able to complete at least two generations per year.